Interaction of space allowance and diet on growth performance and physiological responses of piglets raised in tropical conditions - de Almeida, Guilherme Resende; Hauschild, Luciano [UNESP]; Fraga, Alícia Zem [UNESP]; de Oliveira Littiere, Thayssa [UNESP]; Moreira, Vinicius Eduardo; de Castro Weitzel, Lidianne Carolina; Caetano, Raphael Perini [UNESP]; Lima, Gustavo Freire Resende; Campos, Paulo Henrique Reis Furtado (Springer Nature, 2020)
Intensification of pig production in developing countries has resulted in increased number of animals per unit area leading to welfare and growth performance issues. This study was then performed to evaluate the effects of space allowance and dietary energy and amino acid content on growth performance and physiological parameters of piglets reared under tropical conditions. A total of 1280 piglets (castrated males and females) with initial body weight of 5.9 ± 0.4 kg were used. Animals were distributed in a 2 × 2 factorial arrangement composed by two space allowances (0.30 and 0.22 m2/animal) and two diets during 43 to 63 days of age (control and experimental diet with increased ME and AA content). The experimental period lasted 42 days subdivided into four phases according to the growth stage of the animals: pre-initial I (21 to 27 days of age), pre-initial II (28 to 34 days), initial I (35 to 42 days), and initial II (43 to 63 days). During pre-initial I and II, and initial I phases, pigs housed at a space allowance of 0.30 and 22 m2/animal had similar (P > 0.05) feed intake, weight gain, and feed conversion. During initial phase II, space allowance did not affect (P > 0.05) feed intake nor weight gain of the animals. Whereas, pigs fed the experimental diet had greater weight gain when compared to the control group (530 vs. 515 g/day, P = 0.03). According to our results, reducing space allowance from 0.30 to 22 m2/animal during the nursery phase (21 to 63 days of age) had negligible effects on piglet feed intake and weight gain, whereas feeding piglets with diets containing higher energy and amino levels resulted in greater weight gain.
Keywords: Animal welfare; Lysine; Nursery; Nutrition; Stocking density